The Influence of Environmental, Social, Governance (ESG) Disclosure on Investment Efficiency - Nababan, Rayon; Dwita, Sany (Universitas Negeri Padang, 2024)
Purpose – This study aims to determine the influence of Environmental, Social, and Governance (ESG) disclosure on investment efficiency in the emerging market of Indonesia.Design/methodology/approach – The sample in this study consists of 39 non-financial companies listed on the Indonesia Stock Exchange with ESG scores from Refinitiv Eikon. This study utilizes unbalanced data with 178 firm-year observations and is analyzed using panel regression.Findings – This study's findings diverge from previous research. Our results indicate a significant negative influence of ESG disclosure on investment efficiency. Consequently, increased ESG disclosure can be anticipated as a mechanism of greenwashing. Moreover, ESG disclosure has failed to address agency problems and information asymmetry, leading to a decline in investment efficiency.Originality/value – To the best of the author's knowledge, this research is the first to examine and offer a unique perspective on the relationship between ESG disclosure and investment efficiency by focusing on Indonesia's context as an emerging market. The study not only fills a gap in the existing literature but also provides valuable insights into the specific challenges and opportunities faced by Indonesian companies in implementing ESG practices.Research limitations/implications – Research on ESG disclosure remains limited in Indonesia, primarily because many companies have not yet disclosed their ESG practices, which are also voluntary disclosures. Consequently, the availability of data from companies disclosing ESG information is scarce. This study's findings could motivate companies to adopt more comprehensive and accurate ESG reporting practices aligned with international reporting standards. Furthermore, the findings of this research can contribute to the growing body of ESG (non-financial disclosure) literature, particularly those exploring the potential negative influence of ESG disclosure.